2023
DOI: 10.3390/met13121988
|View full text |Cite
|
Sign up to set email alerts
|

A Review on the Adiabatic Shear Banding Mechanism in Metals and Alloys Considering Microstructural Characteristics, Morphology and Fracture

Konstantina D. Karantza,
Dimitrios E. Manolakos

Abstract: The current review work studies the adiabatic shear banding (ASB) mechanism in metals and alloys, focusing on its microstructural characteristics, dominant evolution mechanisms and final fracture. An ASB reflects a thermomechanical deformation instability developed under high strain and strain rates, finally leading to dynamic fracture. An ASB initially occurs under severe shear localization, followed by a significant rise in temperature due to high strain rate adiabatic conditions. That temperature increase a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 198 publications
(389 reference statements)
1
4
0
Order By: Relevance
“…In this study, T DRX is estimated at 43% of T m , which remains in agreement with relevant work [29]. Finally, when the DRX softening effect is not considered on damage evolution, T cr is set equal to T m in order to capture local melting, which leads to micro-voiding and micro-cracking genesis at the following [1].…”
supporting
confidence: 78%
See 4 more Smart Citations
“…In this study, T DRX is estimated at 43% of T m , which remains in agreement with relevant work [29]. Finally, when the DRX softening effect is not considered on damage evolution, T cr is set equal to T m in order to capture local melting, which leads to micro-voiding and micro-cracking genesis at the following [1].…”
supporting
confidence: 78%
“…Therefore, the actual evaluation of the χ-value has proved crucial in predicting the peak force and ASB evolution, as its typical value of 0.9, which was globally considered during early studies, must be reassessed based on recent findings that highlight its influence from the material and the loading mode [27]. Finally, considering that the DRX temperature of 304SS is estimated at about 720 K and that the minimum examined χ-value of 0.5 for 304SS provides a maximum temperature marginally greater than 720 K, it is indicated that 304SS promotes DRX activation during ASB formation, which is not always guaranteed [1], underlining the importance of accounting for DRX softening effect during numerical computations.…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations